Análisis e interpretación de los estados financieros de la Cooperativa de Ahorro y Crédito Santiago ltda., de la parroquia Santiago - Lozano Lozano, Francisco Paulino (2016)
The thesis entitled: "ANALYSIS AND INTERPRETATION OF FINANCIAL STATEMENTS IN THE COOPERATIVE OF SAVING AND CREDIT “SANTIAGO LTDA.PERIOD 2013 - 2014 ", was held to meet prior to choose the degree of Engineer in Accounting and Auditing, Auditor-Accountant requirement. This research focused on an analysis and interpretation of financial statements period 2013-2014, allowing assessing the financial situation of the Cooperative; this paper presents a theoretical part corresponding to the fundamentals of profitability analysis; and practical, where the scientific method for the application of logical procedures used, obtaining the organization and presentation of results. Financial analysis, the same which began examining the balance sheets of the cooperative is presented; for diagnosis and evaluation vertical analysis was applied, using CAMEL finally indicators by which economic activity of the institution was known. With all developed it was possible to realize that although the cooperative does not have a financial analysis, financial solvency remains acceptable, this allows a normal development of its activities; the conclusions and recommendations should be taken into account so that they can know the status of the institution.